2013
DOI: 10.3109/21691401.2013.794358
|View full text |Cite
|
Sign up to set email alerts
|

Novel multicore niosomes based on double pH-sensitive mixed micelles for Ginsenoside Rh2 delivery

Abstract: In this study, we report the novel double pH-sensitive mixed micelles to fabricate multicore niosomes for drug delivery. The double pH-sensitive mixed micelles (PMM) were prepared with different pH-sensitive polymers, mPEG2000-Hz-CHEMS and mPEG2000-IS (2:1 w/w). Ginsenoside Rh2-loaded DPMM was mixed with Pluronic F-68, in the aqueous medium, and multicore niosomes were fabricated. The size of multicore niosomes were around 100-300 nm with a high encapsulation efficiency of G-Rh2. The G-Rh2-MCN could release en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…With increase in acidity (decreasing pH), percent drug release from the formulation decreased as shown in Figure 6. Interestingly, no abrupt release of drug from the formulation was observed at any pH, confirming the stability of the drugloaded vesicles (Chen et al 2014). Results show stability of this novel surfactant based formulation at physiological pH of blood.…”
Section: Ee% Determinationsupporting
confidence: 64%
“…With increase in acidity (decreasing pH), percent drug release from the formulation decreased as shown in Figure 6. Interestingly, no abrupt release of drug from the formulation was observed at any pH, confirming the stability of the drugloaded vesicles (Chen et al 2014). Results show stability of this novel surfactant based formulation at physiological pH of blood.…”
Section: Ee% Determinationsupporting
confidence: 64%
“…There are some strategies for these purposes. A few studies reported some drug delivery systems by using natural or synthetic vehicles such as liposome and multicore noisome for enhancement of therapeutic indices of Rh2 15 17 . Application of liposome and multicore noisome as drug delivery system is limited by liposomal aggregation and drug leakage.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the types of diseases and lesions, the delivery systems can be modified to target ginsenosides to the specific sites of the body. The targeted delivery of ginsenosides is able to promote their efficient delivery to the site of interest, thereby maximizing the therapeutic efficacy of ginsenosides and also decreasing their possible systemic toxicity [23] , [48] , [50] , [51] . In addition, the administration route of the delivery systems can be varied to avoid the delivery of ginsenosides to unwanted sites and increase the bioavailability [64] , [65] .…”
Section: Factors To Consider For Improving Bioavailability Of Ginsenomentioning
confidence: 99%
“…They have considerably improved the problematic properties of ginsenosides, thereby successfully enhancing their bioavailabilities. The diverse delivery systems have also been administered to the body via different routes to effectively increase the bioavailability of ginsenosides as shown in Table 3 [13] , [35] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] .…”
Section: Introductionmentioning
confidence: 99%